Tetrazolium Staining of Seeds for Interpretation of Viability of Six Indian Tree Species - Gupta, B. N.; Raturi, A. S. (Indian Forester, 1975)
This paper deals with the standardisation of viability test by tetrazolium staining in respect of six Indian tree species viz., Alibizia lebbeck, Albizia procera, Albizia chinensis, Cassia fistula, Cassia nodosa and Pinus roxburghii. Tetrazolium staining is a dependable and accepted biochemical method for testing the inherent germination capacity of a seed lot. This is especially important in forest seeds which take much longer time to germinate or exhibit varying types of dormancy. When soaked in TTZ solution, seeds receive red colour in various patterns depending upon the occurrence of living tissues in them. Attempt has been made to identify viable and non-viable categories of seeds and to standardize the method for their interpretation.